2008
DOI: 10.1103/physreve.77.050801
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physics of a polymer engineering instability: Experiments and computation

Abstract: Entangled polymer melts exhibit a variety of flow instabilities that limit production rates in industrial applications. We present both experimental and computational findings, using flow of monodisperse linear polystyrenes in a contraction-expansion geometry, which illustrate the formation and development of one such flow instability. This viscoelastic disturbance is first observed at the slit outlet and subsequently produces large-scale fluid motions upstream. A numerical linear stability study using the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The original intended use for this model was for computationally demanding calculations such as complex flow geometries. Indeed the model's computational simplicity has been exploited in numerical studies of polymer processing [4][5][6][7][8][9], flow instabilities [10,11], and shear banding [12][13][14][15][16]. However, the relative simplicity of the Rolie-Poly model also makes it amenable to analytic calculation.…”
Section: Introductionmentioning
confidence: 99%
“…The original intended use for this model was for computationally demanding calculations such as complex flow geometries. Indeed the model's computational simplicity has been exploited in numerical studies of polymer processing [4][5][6][7][8][9], flow instabilities [10,11], and shear banding [12][13][14][15][16]. However, the relative simplicity of the Rolie-Poly model also makes it amenable to analytic calculation.…”
Section: Introductionmentioning
confidence: 99%
“…The application of stretch to the molecules within extensional flow at the slit outlet, after their orientation within the shear flow near the walls of the slit, seems to be a possible trigger for the initial instability. Numerical studies based on the linear stability analysis of the ROLIE-POLY model [36] found a similar instability for CE2, the onset of which was observed by either increasing molecular weight of the material (represented by R / d ) or reducing the amount of constraint release. Based on these findings, one possible reason for the failure of either DOW1569 or DOW1568 to go unstable under the flow conditions investigated would be the low constraints placed by individual molecules on adjacent chains.…”
Section: Downstream Initiated Instability For Monodisperse Polystyrenesmentioning
confidence: 82%
“…It is therefore plausible that the mechanism is the same in all three cases. Any predictive tools used to model the monodisperse case (see for example [36]) should accurately capture the instability mechanism present in both the monodisperse and polydisperse polystyrene, allowing a direct insight into instabilities which occur in industrially relevant flows.…”
Section: Processing Of Polydisperse Polystyrene In Various Geometriesmentioning
confidence: 99%
“…Lord et al (2010) further investigated the flow behavior of polydisperse polystyrene for threedimensional case in a similar way, and the multi-mode Rolie-Poly constitutive equation was used in simulation. Hassell et al (2008b) presented the experimental studies of flow instability of the monodisperse linear polystyrenes, and the formation and development of the instability phenomenon are observed. These experimental results were verified using the Rolie-Poly model, and the mechanism between viscoelastic instability and molecular polymer dynamics was discussed by the authors.…”
Section: Introductionmentioning
confidence: 97%